PROFESIOANALISM OF ISLAMIC RELIGION TEACHER TO INCREASE STUDENTSâ LEARNING QUALITY IN STATE SENIOR HIGH SCHOOL 17 SURABAYA - Hasanudin, Wafir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractThis study aims to reveal the Professionalism of Islamic Religious Educationteacher in State Senior High School 17 Surabaya in improving the studentsâlearning quality. As well as improving the studentsâ learning quality in StateSenior High School 17 Surabaya. The method used in this research is analyticaldescriptive research that is a research that aims to give a picture of reality onobject that is studied objectively. The source of the research data obtained fromobservation, interview, questionnaire and documentation. This research tookplace from December 15, 2017 to February 15, 2018. Research proved that theprofessionalism of Islamic Religious Education teacher in State Senior HighSchool 17 Surabaya is good enough. Professional teachers are teachers whocan be mature, able to control themselves, not easily carried away emotions.Be objective, teachers who have academic qualifications in accordance withtheir field of Bachelor of Islamic Religious Education, have four competencies(pedagogic competence, knowledge, personality and social competence). Sothat, studentsâ learning quality will increase and having quality as expected.Â Keywords: Islamic Religious Education Teachers, Professionalism, Quality ofLearning